Internal and external factors influencing the stock prices in construction sector: A study between Malaysia, China and Japan. / Mohamad Hairul Rizuan Ramli - Ramli, Mohamad Hairul Rizuan (2018)
Stock price can be defined as a cost that needs to pay by an investor as a purchasing cost as an exchange on the security of the company. The stock price can be bullish and bearish across the time, which that can be called as the volatility of stock price. While the construction sector can be defined as any company that works on constructing building or infrastructure that use an amount of capital. This study will define the factor that affecting the stock price and will make a comparison between China and Japan to see and compare the performance of Malaysian stock in term of the construction sector. The population for this study is using the annual data for Malaysia, China and Japan for the period of 2013 until 2017 for the stock price, return on equity, economic growth and return on equity. Data of this research play an important role and it must be accurate as it will affect the result of the study. There are several tests which using Ordinary Least Square (OLS) assumptions to measure the relationship between dependent variables and independent variables. This study is expected to find a positive relationship between the dependent variables and independent variables and expected that this independent variable is explain by 95% on the dependent variable.